Efektivitas Alat Peraga Balok Kayu dalam Mendorong Kreativitas Anak Usia Dini: Analisis Pembelajaran dengan Pendekatan Interaktif - Ardhi, Aisha Satira; Warmansyah, Jhoni (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims to investigate the effectiveness of using wooden block educational tools in enhancing the creativity of early childhood children through an interactive approach at TK PPI Kota Payakumbuh. An experimental research method was employed involving an experimental group engaged in playing sessions with the educational tools and a control group without any specific intervention. Data were collected through observations, interviews, and pre- and post-intervention creativity scores. The findings revealed a significant increase in the creativity of early childhood children in the experimental group after the playing sessions, with the average creativity score escalating from 2.8 to 4.2. Conversely, the control group exhibited a lower increase, from 2.7 to 3.1. Observations indicated that children in the experimental group displayed higher engagement in play, developed creative ideas, and engaged in more active interactions with their peers. The utilization of wooden block educational tools within an interactive approach effectively boosted the creativity of early childhood children. Direct interaction with these tools stimulated the children's imagination and abstract thinking abilities. The interactive approach also facilitated the development of problem-solving skills, associative thinking, and self-confidence. The implications of these results are crucial for early childhood education. Educators can leverage these tools to enhance children's creativity through social interaction and creative exploration. Further studies are necessary to gain a more comprehensive understanding of the role of educational tools in fostering creative learning among early childhood children.